The Availability, Pricing, and Affordability of Essential Diabetes Medicines in 17 Low-, Middle-, and High-Income Countries - Babar, Zaheer-Ud-Din; Ramzan, Sara; El-Dahiyat, Faris; Tachmazidis, Ilias; Adebisi, Adeola; Hasan, Syed Shahzad (Frontiers in Pharmacology, 2019)
Background: One third of the world population does not have access to essential medicines. Diabetes require a long-term therapy, which incurs significant health care cost and thus impact access and affordability. This study aims to assess the availability, prices and affordability of four essential medicines used to treat diabetes in private primary care pharmacies in 17 countries. Methods: Data on affordability, availability and prices of four essential diabetes medicines from 51 primary care pharmacies across 17 countries were obtained using a variation of the World Health Organisation/Health Action International (WHO/HAI) methodology. The surveyed countries were Oman, Qatar, Saudi Arabia, United Arab Emirates, China, Jordan, Russia, Armenia, Bangladesh, Egypt, Georgia, India, Pakistan, Sri Lanka, Afghanistan, Nepal and Tanzania. International reference prices and daily income of the lowest-paid unskilled government workers were used as comparators. The prices were converted into US$ using both foreign exchange rates and purchasing power parity. We compared patterns of affordability and availability and prices of Innovator Brand (IB) and Lowest Priced Generic (LPG) of diabetes medicines by WHO regional groupings and by country level. Results: Lowest priced generic of Metformin 500 mg had the highest total mean availability (≥80%) among all the surveyed medicines. The total mean availability of insulin 100 IU/ml was only 36.21% (IBs & LPGs), where IB was more frequently available than LPG (50% vs. 26%) across 17 surveyed countries. Patients would have to spend more to procure one-month’s supply of IB of Insulin in low-income than patients in high-income countries (no. of day’s wages: 2.37 vs. 0.46, p=0.038). For the majority of the surveyed countries the median price-ratio was less than 3. The highest PPP-adjusted prices for 30-day treatment with IB of Insulin 100IU/ml and metformin 500mg were highest in Bangladesh ($80.21) and Tanzania ($4334.17), respectively. Conclusion: Availability of generic form of insulin is poor; IB of insulin was more affordable in high-income countries than low-income countries. Most of the LPGs was reasonably priced and affordable to the lowest-paid unskilled worker.